EFFECT OF STOCKING DENSITY ON GROWTH PERFORMANCE OF DOMESTICATED BARB (Barbonymus balleroides) - Otong Zenal Arifin; Jojo Subagja; Vitas Atmadi Prakoso; Endang Haris Suhud (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
Barb (Barbonymus balleroides) considerably has economic potential as aquaculture commodity. However, there was still lack of development on aquaculture for this species. This study was conducted to observe the effect of different stocking density on growth of barb. The fish (body weight: 14.89 ± 0.13 g) were stocked in nine floating nets (dimension: 2 m x 2 m x 1 m) inside the concrete ponds with three stocking density treatments (10, 15, and 20 fish/m3). Each treatment consisted of three replications. Fish were fed on commercial pellet (30% of crude protein) as much as 3% of the biomass per day with twice a day of feeding frequency. Data of growth performances (body weight, specific growth rate, average daily growth, biomass, food conversion ratio, and survival rate) were collected every 30 days during 90 days of rearing period. Water quality variables (temperature, pH, and dissolved oxygen) were observed during experiment. The results showed that the optimal stocking density for the growth of barb was 10 fish/m3. Best value of food conversion ratio was found 10 fish/m3 compared with 15 and 20 fish/m3 (P<0.05). Meanwhile, there were no significant differences on survival rate between treatments. These results also showed the potential of rearing barb on culture ponds with appropriate stocking density.